Waste gas treatment process in methyl ethyl carbonate production
By using composite adsorbents, including modified activated carbon-PVDF composite materials, modified silica gel-PVDF composite materials, modified activated carbon fibers and modified graphene oxide, the waste gas production of methyl ethyl carbonate is adsorbed and catalytic combustion treatment, which solves the problem of low adsorption rate in the prior art, and achieves efficient exhaust gas purification and long-term adsorption capacity.
Patent Information
- Application Number
- CN202411872826.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-18
AI Technical Summary
In the prior art, the adsorption rate of a single activated carbon to the waste gas for methyl ethyl carbonate production is low, and it is difficult to achieve an adsorption rate of 90% or more.
Compound adsorbents are used, including modified activated carbon-PVDF composite materials, modified silica gel-PVDF composite materials, modified activated carbon fibers and modified graphene oxide. The exhaust gas is adsorbed through the synergistic action of these materials and catalytic combustion treatment is carried out after the hot gas is desorbed.
The adsorption rate of volatile organic matter in the exhaust gas reaches 95.1% or above, the purified organic matter concentration is less than 9mg/m3, which meets the emission standards. The composite adsorbent still maintains high adsorption capacity after multiple thermal desorption and extends its service life.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste gas treatment in carbonate production, in particular to a waste gas treatment process in ethyl methyl carbonate production. Background Art
[0002] During the production of methyl ethyl carbonate (MEC), some waste gas may be generated, which mainly contains organic compounds such as methanol, ethanol and other by-products. In order to ensure environmental protection and factory safety, these waste gases need to be effectively treated. It is a colorless and transparent liquid, insoluble in water, can be used for organic synthesis, and is an excellent solvent for lithium-ion battery electrolyte. It can be synthesized by transesterification reaction between dimethyl carbonate and ethanol under acidic or alkaline catalysts.
[0003] In the production process of ethyl methyl carbonate, some waste gases are generated, which are mainly organic compounds such as methanol, ethanol and other by-products. In order to ensure environmental protection and factory safety, these waste gases need to be effectively treated.
[0004] Currently, the treatment methods that can be used for these waste gases include combustion treatment, adsorption treatment, condensation and liquid absorption, biodegradation and chemical absorption.
[0005] Among the above methods, adsorption treatment is the most common. In the prior art, the waste gas from the synthesis process of ethyl methyl carbonate is often adsorbed by activated carbon, which can effectively absorb organic compounds. However, in actual adsorption, it is found that the adsorption capacity of waste gas by granular activated carbon alone is limited. Its adsorption rate for waste gas is generally less than 90%, and in most cases it is 75%-85%, which is difficult to reach 90% or even higher adsorption rate. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a waste gas treatment process in the production of ethyl methyl carbonate, which can achieve a treatment efficiency (i.e., the absorption rate of volatile organic compounds) of 95.1% or above in organic waste gas.
[0007] The technical purpose of the present invention is achieved through the following technical solutions: A waste gas treatment process in the production of ethyl methyl carbonate, firstly, the waste gas is passed into an adsorption tower, and is adsorbed by a composite adsorbent in the adsorption tower; then, the composite adsorbent in the adsorption tower is desorbed by hot gas; finally, the desorbed gas is subjected to catalytic combustion treatment; The composite adsorbent includes modified activated carbon-PVDF composite material, modified silica gel-PVDF composite material, modified activated carbon fiber, and modified graphene oxide.
[0008] Wherein, the modified activated carbon-PVDF composite material is formed by grafting hydrophilic monomers on the surface of the activated carbon-PVDF composite material; The modified silica gel-PVDF composite material is formed by grafting hydrophilic monomers on the surface of the silica gel-PVDF composite material; The modified activated carbon fiber is obtained by first grafting vinyl alcohol onto activated carbon fiber and then introducing disulfide bonds: The modified graphene oxide is obtained by grafting graphene oxide with polyvinyl alcohol.
[0009] As some possible implementation methods of the present application, the weight proportions of the components in the composite adsorbent are as follows: 100-120 parts of modified activated carbon-PVDF composite material, 20-40 parts of modified silica gel-PVDF composite material, 10-25 parts of modified activated carbon fiber, and 10-25 parts of modified graphene oxide.
[0010] As some possible implementation methods of the present application, the weight proportions of the components in the composite adsorbent are as follows: 105-118 parts of modified activated carbon-PVDF composite material, 25-30 parts of modified silica gel-PVDF composite material, 13-22 parts of modified activated carbon fiber, and 12-20 parts of modified graphene oxide.
[0011] As some possible implementation methods of the present application, the weight proportions of the components in the composite adsorbent are as follows: 115 parts of modified activated carbon-PVDF composite material, 27 parts of modified silica gel-PVDF composite material, 20 parts of modified activated carbon fiber, and 18 parts of modified graphene oxide.
[0012] As some possible implementation modes of the present application, the PVDF material in the modified activated carbon-PVDF composite material and the modified silica gel-PVDF composite material includes PVDF powder and PTFE powder.
[0013] As some feasible implementation methods of the present application, the mass ratio of the PVDF powder to the PTFE powder is 10:1~3.
[0014] As some possible implementation methods of the present application, the hydrophilic monomer is any one of methacrylic acid, acrylic acid, acrylamide and methacrylamide.
[0015] As some possible implementation modes of the present application, the mesh size of the activated carbon and the silica gel is 4-30 mesh.
[0016] As some possible implementation methods of the present application, the preparation method of the modified activated carbon-PVDF composite material is as follows: S1. First, a PVDF material is added to N, N-dimethylacetamide and mixed thoroughly to prepare a PVDF dispersion, and then activated carbon is added to the PVDF dispersion and ultrasonically dispersed for 20-50 minutes, and then the organic solvent is removed and dried at 100-150°C in a nitrogen atmosphere for 2-5 hours to obtain an activated carbon-PVDF composite material; S2. The hydrophilic monomer is evenly sprayed onto the surface of the activated carbon-PVDF composite material, which is then placed in a stoppered glass bottle and irradiated with 60 Co-γ rays to obtain a modified activated carbon-PVDF composite material.
[0017] As some possible implementation methods of the present application, the mass ratio of the PVDF material, N,N-dimethylacetamide and activated carbon is 18: (300-350): (80-100).
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention provides a composite adsorbent comprising a modified activated carbon-PVDF composite material, a modified silica gel-PVDF composite material, a modified activated carbon fiber, and a modified graphene oxide, which can effectively adsorb the waste gas in the production of ethyl methyl carbonate. According to the test, the adsorption rate of the composite adsorbent provided by the present invention on volatile organic matter in the waste gas is not less than 95.1%, and the concentration of organic matter after purification is less than 9 mg / m 3 , meeting emission standards.
[0019] 2. The present invention can effectively improve the high temperature resistance and high temperature deformation resistance of PVDF material by adding PTFE powder to PVDF material, ensure that the PVDF material will not show obvious deformation during the hot gas desorption stage, and effectively avoid the swelling problem of PVDF material caused by carbonate substances in the exhaust gas, thereby effectively avoiding thermal deformation of modified activated carbon-PVDF composite material and modified silica gel-PVDF composite material in the high temperature stage, and effectively improving the service life of the composite adsorbent.
[0020] 3. After the seventh thermal desorption treatment, the composite adsorbent provided by the present invention still has an adsorption rate higher than 80% and a fragmentation degree lower than 10%. This indicates that the composite adsorbent provided by the present invention can maintain a high adsorption capacity for waste gas for a long time, and at the same time has extremely strong mechanical properties, which can significantly reduce the degree of fragmentation during adsorption and thermal desorption, and effectively extend the service life. DETAILED DESCRIPTION
[0021] At present, single activated carbon particles are often used to adsorb waste gas in the synthesis process of ethyl methyl carbonate. However, the adsorption rate of waste gas is generally lower than 90%, and in most cases it is 75%-85%, which makes it difficult to reach 90% or even higher adsorption rate.
[0022] Based on this, the present invention provides a waste gas treatment process in the production of ethyl methyl carbonate, comprising the following steps: A waste gas treatment process in the production of ethyl methyl carbonate, firstly, the waste gas is passed into an adsorption tower, and is adsorbed by a composite adsorbent in the adsorption tower; then, the composite adsorbent in the adsorption tower is desorbed by hot gas; finally, the desorbed gas is subjected to catalytic combustion treatment; The composite adsorbent includes modified activated carbon-PVDF composite material, modified silica gel-PVDF composite material, modified activated carbon fiber, and modified graphene oxide.
[0023] Wherein, the modified activated carbon-PVDF composite material is formed by grafting hydrophilic monomers on the surface of the activated carbon-PVDF composite material; The modified silica gel-PVDF composite material is formed by grafting hydrophilic monomers on the surface of the silica gel-PVDF composite material; The modified activated carbon fiber is obtained by first grafting vinyl alcohol onto activated carbon fiber and then introducing disulfide bonds: The modified graphene oxide is obtained by grafting graphene oxide with polyvinyl alcohol.
[0024] In the above scheme, the volatile organic compounds in the exhaust gas are firstly adsorbed by the composite adsorbent, and then the adsorbed volatile organic compounds are catalytically burned by desorption to achieve the purpose of purifying the exhaust gas.
[0025] In the above scheme, the research and development ideas of composite adsorbents are as follows: Activated carbon is prone to compaction during the long-term adsorption of exhaust gas. After compaction, it is difficult for the activated carbon to continue to effectively perform adsorption operations. Therefore, the service life of activated carbon is generally short (no more than 3 months). In addition, due to the poor mechanical strength of activated carbon and the existence of slight compaction and other problems, it is very easy to break during the thermal desorption process of activated carbon, causing its pores to be severely damaged. Based on this, the adsorption effect of activated carbon after thermal desorption is greatly reduced.
[0026] In addition, in the production process of ethyl methyl carbonate, in addition to methanol or ethanol, carbonate substances are also contained, and carbonate substances are usually polar molecules, and the adsorption capacity of activated carbon to them is relatively poor. Therefore, in addition to using activated carbon as the main adsorbent, silica gel is also added, because the surface contains a large number of silicon-oxygen bonds and has a porous structure that makes it easy to adsorb organic compounds, including carbonate compounds. However, the mechanical properties of silica gel itself, such as tensile strength and tear strength, are relatively poor, so it is very easy to deform due to mutual extrusion during the adsorption process, and it will also burst due to improper temperature control during the thermal desorption process, which seriously affects its adsorption effect.
[0027] Based on this, it is necessary to modify the activated carbon and silica gel, as follows: The present invention first mixes activated carbon and silica gel with PVDF material respectively to prepare activated carbon-PVDF composite materials and silica gel-PVDF composite materials. The introduction of PVDF material can effectively improve the mechanical strength of activated carbon and silica gel, improve the anti-caking performance of activated carbon and the high-temperature crack resistance of silica gel, so that the composite adsorbent can greatly reduce the degree of breakage during regeneration treatment and effectively extend the service life.
[0028] However, in activated carbon-PVDF composite materials and silica gel-PVDF composite materials, PVDF material will occupy part of the pores and surface structure inside the activated carbon and silica gel, resulting in a reduction in the adsorption sites on the surface and inside of the activated carbon and silica gel, thereby reducing the overall adsorption capacity of the composite adsorbent.
[0029] Based on this, the present invention grafts hydrophilic monomers on the surface of PVDF materials to prepare modified activated carbon-PVDF composite materials and modified silica gel-PVDF composite materials, wherein the grafted hydrophilic monomers contain hydrophilic groups such as hydroxyl groups, which can effectively improve the adsorption effect of hydrophilic organic matter such as methanol and ethanol.
[0030] However, in modified activated carbon-PVDF composite materials and modified silica gel-PVDF composite materials, hydrophilic monomers are concentrated on the surface of activated carbon or silica gel. Although the adsorption effect on organic matter can be greatly improved, the hydrophilic monomers will produce certain obstacles on the surface of activated carbon or silica gel, resulting in difficulty in effectively transporting volatile organic matter to activated carbon and silica gel, resulting in reduced contact opportunities between volatile organic matter and activated carbon and silica gel, which in turn leads to reduced adsorption efficiency.
[0031] Based on this, the present invention adds activated carbon fiber, which not only has extremely high adsorption performance for organic matter such as methanol and ethanol, but also can be interspersed between modified activated carbon-PVDF composite materials, between modified silica gel-PVDF composite materials, and between modified activated carbon-PVDF composite materials and modified silica gel-PVDF composite materials, that is, the activated carbon fiber can pass through the hydrophilic monomer and connect with the activated carbon or silica gel, and then build a transmission channel between the activated carbons, between the silica gels, or between the activated carbon and the silica gel, so that volatile organic matter can be transmitted along the transmission channel to the inside of the activated carbon and the silica gel, thereby increasing the contact opportunity between the exhaust gas and the activated carbon and the silica gel, and thus improving the adsorption effect.
[0032] However, because the activated carbon fiber itself is relatively soft, under the heavy pressure of the particle components such as the modified activated carbon-PVDF composite material and the modified silica gel-PVDF composite material, the activated carbon fiber will be gradually compressed, causing the pores inside it to become smaller, seriously affecting the adsorption effect.
[0033] Based on this, the present invention introduces polyvinyl alcohol on the surface of activated carbon fiber, which can form a network structure on the surface of activated carbon fiber, thereby playing a certain buffering role on the heavy pressure of the particle components, thereby reducing the degree of compression of the activated carbon fiber; at the same time, the hydroxyl structure in polyvinyl alcohol can also improve the adsorption effect on hydrophilic organic matter such as methanol and ethanol.
[0034] Although the above-mentioned methacrylamide monomer and polyvinyl alcohol can improve the adsorption capacity of organic matter, it is also equivalent to forming multiple layers of obstacles on the outside of activated carbon and silica gel, which has an adverse effect on the adsorption performance of activated carbon and silica gel.
[0035] Based on this, the present invention continues to introduce disulfide bonds on the activated carbon fibers. The introduced disulfide bonds can not only further improve the compression and buffering resistance of the activated carbon fibers, so as to further solve the compression problem of the activated carbon fibers and improve the adsorption effect of the activated carbon fibers, but also, due to the introduction of disulfide bonds, they can be interspersed between the polyvinyl alcohol groups or hydrophilic groups, thereby increasing the distance between adjacent polyvinyl alcohol groups and adjacent hydrophilic monomers, thereby reducing the degree of obstruction of the polyvinyl alcohol groups and hydrophilic monomers to the activated carbon and silica gel, and significantly improving the contact opportunity between volatile organic matter and activated carbon and silica gel.
[0036] Finally, on the basis of the above components, modified graphene oxide is added. Its layered structure can form a waste gas transport channel. At the same time, it has a strong adsorption performance for waste gas and can also fill the gaps between the above particle components, effectively improving the composite adsorbent's capture of waste gas and further improving the adsorption capacity. At the same time, the polyvinyl alcohol group in the modified graphene can form hydrogen bonds with the same groups in other components, thereby effectively improving its binding ability with other components. At the same time, it can effectively solve the problem of its own agglomeration and further solve the problem of the composite adsorbent's hardening.
[0037] Through the synergistic effect of the above components, the prepared composite adsorbent can effectively adsorb the waste gas in the production of ethyl methyl carbonate. After testing, the adsorption rate of the composite adsorbent provided by the present invention for waste gas is not less than 95.1%, and the organic matter concentration after purification is less than 9 mg / m 3 , meeting emission standards.
[0038] In order to further improve the high temperature resistance and high temperature resistance to deformation of the composite adsorbent, as some of the embodiments of the present application, the components of the PVDF material are further limited, and the PVDF material in the modified activated carbon-PVDF composite material and the modified silica gel-PVDF composite material includes PVDF powder and PTFE powder. Because the melting point of PVDF material is 172°C, the heat deformation temperature is 112~145°C, and it is easy to swell under the action of carbonate, although its melting point and heat deformation temperature have changed after the grafting of hydrophilic monomers, in order to enable the subsequent multiple thermal desorption to proceed smoothly, some PTFE powder is added to the PVDF material, which can significantly improve the high temperature resistance and melting point of the PVDF material, thereby ensuring the smooth subsequent thermal desorption, and at the same time ensuring that after multiple thermal desorptions, the modified activated carbon-PVDF composite material and the modified silica gel-PVDF composite material will not undergo obvious thermal deformation.
[0039] The waste gas treatment process in the production of ethyl methyl carbonate described in the present application is further described in detail below in conjunction with specific implementation methods.
[0040] Example 1 The waste gas from the production of ethyl methyl carbonate is passed into an adsorption tower equipped with an air flow distributor and a composite adsorbent for purification, and the purified gas meets emission standards; thereafter, the organic matter adsorbed in the composite adsorbent is desorbed by hot air, and the desorbed gas is subjected to catalytic combustion treatment to meet emission standards.
[0041] The exhaust gas temperature entering the adsorption tower is 20-30°C, and the air flow rate is 0.8m 3 / s.
[0042] Wherein, the composite adsorbent comprises the following components in parts by weight: 119 parts of modified activated carbon-PVDF composite materials, 22 parts of modified silica gel-PVDF composite materials, 19 parts of modified activated carbon fibers, and 15 parts of modified graphene oxide.
[0043] Wherein, the preparation method of the above components is as follows: ① The preparation method of modified activated carbon-PVDF composite material is as follows: S1. First, add PVDF material into N, N-dimethylacetamide and mix them thoroughly to prepare a PVDF dispersion, then add 4-10 mesh activated carbon into the PVDF dispersion and disperse it by ultrasound (ultrasonic frequency is 40KHz, power is 200W) at 35-45°C for 30 minutes, then remove the organic solvent, dry it at 125°C in a nitrogen atmosphere for 3.5 hours to obtain an activated carbon-PVDF composite material; wherein the mass ratio of the PVDF material, N, N-dimethylacetamide and activated carbon is 18:320:95.
[0044] S2. 8% hydrophilic monomer of the total mass of PVDF is uniformly sprayed onto the activated carbon-PVDF composite material, and then packed together in a stoppered glass bottle, and irradiated with 60 Co-γ rays (irradiation dose rate is 25Gy / h, irradiation dose is 50kGy) to obtain a modified activated carbon-PVDF composite material.
[0045] ② The preparation method of modified silica gel-PVDF composite material is as follows: S1. First, PVDF material is added to N, N-dimethylacetamide and mixed thoroughly to prepare a PVDF dispersion, then 8-20 mesh silica gel is added to the PVDF dispersion and dispersed at 35-45°C by ultrasound (ultrasonic frequency is 40KHz, power is 200W) for 30 minutes, then the organic solvent is removed, and the mixture is dried at 125°C in a nitrogen atmosphere for 3.5 hours to obtain a silica gel-PVDF composite material; wherein the mass ratio of the PVDF material, N, N-dimethylacetamide and silica gel is 18:320:95.
[0046] S2. 8% acrylic acid monomer of the total mass of PVDF was uniformly sprayed onto the silica gel-PVDF composite material, and then placed together in a stoppered glass bottle and irradiated with 60 Co γ-rays to obtain a modified silica gel-PVDF composite material.
[0047] ③The preparation method of modified activated carbon fiber is as follows: S1: 175 g N,N-dimethylformamide, 5 g activated carbon carbon fiber, 100 g polyvinyl alcohol and 1.5 g toluene diisocyanate were added to a reaction bottle and reacted at 45° C. for 10 h, followed by filtering, washing and drying to obtain the first modified activated carbon fiber; S2: adding 150 g / L (3-mercaptopropyl) triethoxysilane to a 90% ethanol solution, followed by shaking at 30°C for 60 min, then adding the first modified activated carbon fiber to the solution, padding and baking at 120°C for 2 min to obtain the second modified activated carbon fiber; Prepare 100g / L α-lipoic acid solution, add 100g / L anhydrous sodium sulfite to reduce and dissolve α-lipoic acid, then add 3g / L penetrant JFC to obtain finishing solution, and immerse the second modified activated carbon fiber in the finishing solution, and put it into a steamer after padding, the steaming temperature is 120°C, and the time is 20min. After steaming, oxidize under constant tension ventilation for 6h to obtain the modified activated carbon fiber.
[0048] ④The preparation method of modified graphene oxide is as follows: 175 g of N,N-dimethylformamide, 5 g of graphene oxide (sheet size is 50 nm to 200 nm), 80 g of polyvinyl alcohol and 1.5 g of toluene diisocyanate were added into a reaction bottle and reacted at 45° C. for 10 h, followed by filtering, washing and drying to obtain the first modified activated carbon fiber.
[0049] Example 2 Compared with Example 1, only the amount of each component in the composite adsorbent is changed, and the other processes and process parameters are the same. The amount of each component after the change is as follows: 118 parts of modified activated carbon-PVDF composite material, 25 parts of modified silica gel-PVDF composite material, 20 parts of modified activated carbon fiber, and 15 parts of modified graphene oxide.
[0050] Example 3 Compared with Example 1, only the amount of each component in the composite adsorbent is changed, and the other processes and process parameters are the same. The amount of each component after the change is as follows: 115 parts of modified activated carbon-PVDF composite material, 27 parts of modified silica gel-PVDF composite material, 20 parts of modified activated carbon fiber, and 18 parts of modified graphene oxide.
[0051] Example 4 Compared with Example 1, only the PVDF material in the modified activated carbon-PVDF composite material and the modified silica gel-PVDF composite material is replaced with a mixed material of PVDF powder and PTFE powder, wherein the mass ratio of the two is 10:1.5. The rest of the processes and process parameters are the same as those in Example 1.
[0052] Comparative Example 1 The composite adsorbent is only 4-10 mesh activated carbon.
[0053] Comparative Example 2 The composite adsorbent is a mixture of 4-10 mesh activated carbon and 8-20 mesh silica gel, and the mass ratio of the two is 120:22.
[0054] Comparative Example 3 Compared with Example 1, only the types of components in the composite adsorbent were changed, and the other processes and process parameters were the same. The components after the changes are as follows: 120 parts of activated carbon-PVDF composite material, 22 parts of silica gel-PVDF composite material, 19 parts of activated carbon fiber, and 15 parts of graphene oxide.
[0055] Comparative Example 4 Compared with Example 1, only the types of components in the composite adsorbent were changed, and the other processes and process parameters were the same. The components after the changes are as follows: 144 parts of modified activated carbon-PVDF composite materials and 19 parts of modified activated carbon fibers.
[0056] Experimental Example 1: The adsorption rate of the composite adsorbent on waste gas when it is used for the first time.
[0057] The VOCs concentration of the exhaust gas entering the adsorption box and the VOCs concentration of the gas after purification by the adsorption box were tested respectively to determine the adsorption rate of the exhaust gas when the composite adsorbent was used for the first time. The adsorption rate (%) = [(VOCs concentration before purification - VOCs concentration after purification) / VOCs concentration before purification] × 100%.
[0058] Among them, in this experimental example, except for the slight difference in the concentration of volatile organic matter when the exhaust gas enters the tower, other conditions, such as the exhaust gas adsorption time, intake speed, intake temperature, intake speed, shape and size of the adsorption tower and other external conditions are the same. The test results are shown in Table 1.
[0059] Table 1 It can be seen from Table 1 that the composite adsorbent in Examples 1-3 has a strong adsorption effect on the waste gas in the production of ethyl methyl carbonate. Specifically, the adsorption rate is not less than 95.1%, and the concentration of volatile organic matter after adsorption by the composite adsorbent is less than 9 mg / m 3 , meeting emission requirements.
[0060] In Comparative Examples 1 and 2, a single activated carbon or a mixture of activated carbon and silica gel is used as the adsorbent, and the adsorption effect thereof is inferior to that of the present invention, and the adsorption rate thereof does not reach 90%.
[0061] In Comparative Example 3, the component materials were not modified, and the final adsorption effect was not much different from that of Comparative Example 2, and did not reach 90%.
[0062] The composite adsorbent in Comparative Example 4 has an improved adsorption effect compared to Examples 1-3, with an adsorption rate greater than 90%. However, compared to Examples 1-4, its adsorption rate is still relatively low.
[0063] It can be seen from Comparative Examples 3 and 4 that the composite adsorbents that are not strictly configured according to the component dosage or component type provided by the present invention have reduced adsorption effects.
[0064] Experimental Example 2: Testing the adsorption rate of the adsorbent after multiple thermal desorptions.
[0065] The time point of each thermal desorption of the adsorbent in Examples 1-4 and Comparative Examples 1-4 is the same, and the thermal desorption adopts the existing technology.
[0066] Among them, after 7 thermal desorptions, the adsorption rate of the composite adsorbent in Examples 1-3 is greater than 80%, and the breakage rate of the activated carbon-PVDF composite material and the silica gel-PVDF composite material in the composite adsorbent does not exceed 15%.
[0067] After 7 thermal desorptions, the composite adsorbent in Example 4 has an adsorption rate of >80%, and the crushing rate of the activated carbon-PVDF composite material and the silica gel-PVDF composite material in the composite adsorbent does not exceed 10%. It can be seen that the composite adsorbent in Example 4 can greatly reduce the crushing degree of the composite adsorbent due to the addition of PTFE powder, which is specifically manifested in that the deformation degree of the two composite materials is effectively improved during the thermal desorption stage, and the explosion degree of silica gel is effectively improved. At the same time, due to the improvement of the mechanical strength of the composite adsorbent, the degree of crushing between components caused by heavy pressure during the adsorption process can be significantly improved.
[0068] Among them, the composite adsorbent of Examples 1-4 did not show any agglomeration phenomenon during the entire process from the first adsorption to the seventh thermal desorption.
[0069] In Comparative Example 1, after three thermal desorptions, the adsorption rate of the adsorbent was less than 60%, and the activated carbon breakage rate was greater than 40%. The adsorbent could no longer continue to adsorb after three thermal desorptions and needed to be replaced. Among them, the activated carbon in Comparative Example 1 had already had a hardening problem before the third thermal desorption.
[0070] In Comparative Example 2, after thermal desorption for 3 times, the adsorption rate of the adsorbent was less than 60%, and the overall breakage rate of the adsorbent was greater than 40%, and the silica gel was more damaged because it was easy to explode during the thermal desorption process. After thermal desorption for 3 times, the adsorbent could no longer continue to adsorb and needed to be replaced.
[0071] After 4 thermal desorptions, the adsorption rate of the adsorbent in Comparative Example 3 was less than 65%, and the overall breakage rate of the two composite materials was less than 10%. The reason for the low breakage was the protective effect of PVDF on activated carbon and silica gel, which greatly reduced the breakage of the two composite materials. However, some pores and surface structures of both activated carbon and silica gel were blocked by PVDF materials, resulting in a decrease in their adsorption sites. At the same time, the activated carbon fibers with high adsorption capacity collapsed and compressed during long-term heavy pressure, which led to the destruction of the pore structure, thereby reducing the overall adsorption capacity of the composite adsorbent.
[0072] After 7 thermal desorptions, the adsorbent in Comparative Example 4 had an adsorption rate of less than 70%, and a composite material breakage rate of <10%. In this comparative example, since no silica gel-PVDF composite material and modified graphite oxide were provided, the overall adsorption effect was inferior to that of Examples 1-4. However, due to the protective effect of PVDF material on activated carbon, the breakage of the material was greatly reduced.
[0073] In summary: the composite adsorbent in Examples 1-4 not only has a strong adsorption effect on volatile organic compounds in the exhaust gas during the first operation, but also still has a good adsorption effect after 7 thermal desorptions, effectively improving the service life.
Claims
1. A process for treating waste gas in the production of ethyl methyl carbonate, characterized in that: First, the waste gas is passed into the adsorption tower and adsorbed by the composite adsorbent in the adsorption tower; then the composite adsorbent in the adsorption tower is desorbed by hot gas; finally, the desorbed gas is subjected to catalytic combustion treatment; Wherein, the composite adsorbent includes modified activated carbon-PVDF composite material, modified silica gel-PVDF composite material, modified activated carbon fiber, and modified graphene oxide; Wherein, the modified activated carbon-PVDF composite material is formed by grafting hydrophilic monomers on the surface of the activated carbon-PVDF composite material; The modified silica gel-PVDF composite material is formed by grafting hydrophilic monomers on the surface of the silica gel-PVDF composite material; The modified activated carbon fiber is obtained by first grafting vinyl alcohol onto activated carbon fiber and then introducing disulfide bonds: The modified graphene oxide is obtained by grafting graphene oxide with polyvinyl alcohol.
2. The process for treating waste gas in the production of ethyl methyl carbonate according to claim 1, characterized in that: The weight proportions of each component in the composite adsorbent are as follows: 100-120 parts of modified activated carbon-PVDF composite material, 20-40 parts of modified silica gel-PVDF composite material, 10-25 parts of modified activated carbon fiber, and 10-25 parts of modified graphene oxide.
3. The process for treating waste gas in the production of ethyl methyl carbonate according to claim 2, characterized in that: The weight proportions of each component in the composite adsorbent are as follows: 105-118 parts of modified activated carbon-PVDF composite material, 25-30 parts of modified silica gel-PVDF composite material, 13-22 parts of modified activated carbon fiber, and 12-20 parts of modified graphene oxide.
4. The process for treating waste gas in the production of ethyl methyl carbonate according to claim 2, characterized in that: The weight proportions of each component in the composite adsorbent are as follows: 115 parts of modified activated carbon-PVDF composite material, 27 parts of modified silica gel-PVDF composite material, 20 parts of modified activated carbon fiber, and 18 parts of modified graphene oxide.
5. The process for treating waste gas in the production of ethyl methyl carbonate according to claim 1, characterized in that: The PVDF material in the modified activated carbon-PVDF composite material and the modified silica gel-PVDF composite material includes PVDF powder and PTFE powder.
6. The process for treating waste gas in the production of ethyl methyl carbonate according to claim 5, characterized in that: The mass ratio of the PVDF powder to the PTFE powder is 10:1-3.
7. The process for treating waste gas in the production of ethyl methyl carbonate according to claim 1, characterized in that: The hydrophilic monomer is any one of methacrylic acid, acrylic acid, acrylamide and methacrylamide.
8. The process for treating waste gas in the production of ethyl methyl carbonate according to claim 1, characterized in that: The mesh numbers of the activated carbon and the silica gel are 4-30 meshes.
9. The process for treating waste gas in the production of ethyl methyl carbonate according to claim 1, characterized in that: The preparation method of the modified activated carbon-PVDF composite material is as follows: S1. First, a PVDF material is added to N, N-dimethylacetamide and mixed thoroughly to prepare a PVDF dispersion, and then activated carbon is added to the PVDF dispersion and ultrasonically dispersed for 20-50 minutes, and then the organic solvent is removed and dried at 100-150°C in a nitrogen atmosphere for 2-5 hours to obtain an activated carbon-PVDF composite material; S2. The hydrophilic monomer is evenly sprayed onto the surface of the activated carbon-PVDF composite material, which is then placed in a stoppered glass bottle and irradiated with 60Co-γ rays to obtain a modified activated carbon-PVDF composite material.
10. The process for treating waste gas in the production of ethyl methyl carbonate according to claim 9, characterized in that: The mass ratio of the PVDF material, N,N-dimethylacetamide and activated carbon is 18: (300-350): (80-100).
Citation Information
Patent Citations
Carbon nanotube composite material sewage processing reagent and processing method
CN108059297A
Hydrophilic high-strength retention crease-resistant finishing method for cellulosic fiber fabric
CN112921653A
Spraying organic waste gas treatment process
CN118788097A
High-difficulty degradation-resistant salt-containing wastewater treatment equipment and process
CN118812107A
Gas-phase material recovery device of methyl ethyl carbonate system
CN221333449U